Drumul păsărilor . Birds Road - Trencsényi, Klára; Năumescu, Vlad (Libra Film, 2009)
Verzio FF Submission In the Danube Delta, in Periprava, the old ones die and the traditions are lost. The Lipovan community, made up of old-rite believers, has remained without a priest. The priest has always been chosen from the community and he did not need to have studied theology. Now, the old priest is ill and the new one cannot take care of his duties because he is unmarried and there is no girl willing to become a priest’s wife. The villagers are desperate – funerals are performed by the deacon, and the Easter and Christmas services are also held without a priest. The films follows three years of the community’s life, where recent changes and modernization unveil the fragility and vulnerability of a traditional society.